Development of polymeric micelles loaded with STAT3 inhibitory, Stattic, for cancer treatment - Hamed Masoumzadeh; Nasrin Hoseinzad; Sevda Jafari; Ali Shayanfar; Haleh Vaez; Ommoleila Molavi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Background. STAT3 is an oncogenic signaling pathway found constitutively active in many types of human malignancies and plays a key role in cancer progression. Stattic is a small molecule, which selectively inhibits the SH2 domain of STAT3. In most studies, stattic has been proposed as a promising strategy STAT3 inhibition in cancer cells harboring constitutively active STAT3. However, the lack of proper formulation due to the poor water solubility and low bioavailability of stattic is a major limitation for its usage in the clinic. This project aimed to develop poly(ethylene glycol)-block-poly(caprolactone) (PEG-b-PCL)-based polymeric micelles loaded with stattic and evaluate drug encapsulation efficiency and release in the developed formulations. Methods. In this experimental study, to prepare stattic loaded micellar formulations, the co-solvent evaporation method was used. The mean diameter and polydispersity index (PDI) of micelles were defined by the light scattering method. Encapsulated drug levels were measured using high-performance liquid chromatography (HPLC). Data were analyzed using GraphPad Prism software through one-way ANOVA. Results. Stattic was loaded in the polymeric micelles with encapsulation efficiency ranging from 40% to 73%. Drug loaded micelles were measured between 90 to 130 nm in size. PDI was obtained 0.3-1, and encapsulation of stattic in Polyethylene glycol-block-poly (α-benzyl carboxylate ε-caprolactone (PEG-b-PBCL) micellar formulation resulted in a more than 6-fold increase in the water solubility of stattic (0.36 vs. 0.06 mg/mL). Regarding high encapsulation efficiency, two micellar formulations were selected for further analysis in that both of them released 70-80% of the drug within the first hour, indicating burst release of the drug. Conclusion. These findings show that PEG-b-PBCL copolymers can be a suitable vehicle for the solubilization of stattic.